Characteristics of Exemplary Programs in Preparing Graduate Assistants to Teach Economics. (May 2014) - Milkman, Martin; McCoy, James
Recent research by Walstad and Becker (2010) and McCoy and Milkman (2010) indicate that the vast majority of economics graduate programs perform an inadequate job of training their Ph.D. students to teach. In this paper we report survey data from nine schools often identified as having exemplary programs in preparing graduate students to teach economics. The first part of the survey asked general questions concerning the forms of teacher training and preparation for doctoral economics students; specifically, what are they doing and how are they doing it? The second set of the questions asked whether or not certain topics are addressed during the training, whether there is direct supervision and/or evaluation of doctoral student teaching, and if there is an evaluation of the effectiveness of their teacher training programs. After summarizing the responses to the queries, we note that while successful programs do not adhere to a standard instructional format there is widespread agreement about the content the programs should provide.